2015
DOI: 10.1515/jeb-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Econometric Analysis of Croatia’s Proclaimed Foreign Exchange Rate

Abstract: The officially proclaimed foreign exchange policy of the Croatian National Bank (CNB) is a managed float with a discretionary right of intervention on the Croatian kuna/euro foreign exchange (FX)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Following unit root tests results for the variables quarterly GDP growth rate and foreign exchange rate, these two variables are stationary at its levels. Mance et al (2015) found the EUR/HRK foreign exchange rate stationary at this level as well. Taking into account the aforementioned unitroot tests results, to estimate the equation an autoregressive distributed lag (ARDL) modeling approach is used.…”
Section: Research Data and Methodologymentioning
confidence: 64%
“…Following unit root tests results for the variables quarterly GDP growth rate and foreign exchange rate, these two variables are stationary at its levels. Mance et al (2015) found the EUR/HRK foreign exchange rate stationary at this level as well. Taking into account the aforementioned unitroot tests results, to estimate the equation an autoregressive distributed lag (ARDL) modeling approach is used.…”
Section: Research Data and Methodologymentioning
confidence: 64%
“…Recalling the results from Bošnjak (2018) among others, there is a prominent financial euroisation in Croatian financial system limiting the space for nominal depreciation of Croatian kuna against euro. The other possibility to influence price competitiveness would be management inflation but it seems as a second goal of monetary authorizes (Mance et al 2015). Furthermore, Croatia has been EU member country since the 2013 and Bošnjak et al (2019) illustrated convergence of import prices between Croatia and EMU members.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…They also must take into account the level of international reserves that are considered supportive of the credibility of the peg exchange rate arrangement (El Hamiani Khatat et al 2020). The exchange rate targeting countries may face some operational and policy challenges, including the necessity for supportive fiscal policy, and a strengthened and coherent monetary policy framework (see, for instance, Mance et al 2015) for an indepth discussion on this particular aspect for the case of Croatia), the optimal choice of monetary policy reaction function, development, and implementation of sound strategies on managing interest rate and exchange rate and selection of liquidity management framework (El Hamiani Khatat et al 2020).…”
Section: Introductionmentioning
confidence: 99%